PRINCIPLE OF THE PRIORITY OF CHILDREN'S RIGHTS AND INTEREST - Esanova Zamira Normurotovna (PT. Antis International Publisher, 2024)
Objective: This study examines the legal framework of parental rights and obligations in Uzbekistan, emphasizing how it protects children’s welfare. The research focuses on judicial practices, institutional roles, and adherence to the best interests of the child principle. Method: A normative legal approach supported by descriptive analysis is applied, including legal framework reviews, content analysis of judicial practices, and comparative legal studies. The study categorizes disputes into custody, adoption, and termination of parental rights, analyzing factors like emotional attachment, living conditions, and children’s preferences. Results: The findings reveal that Uzbek laws and courts prioritize the best interests of the child, emphasizing emotional and developmental well-being over material conditions. Judicial decisions consider children’s opinions, especially as they grow older, and systematically classify parental disputes. Institutional actors, like the Deputy Ombudsman for Children’s Rights, play a critical role in safeguarding these rights. Novelty: This research highlights the integration of international standards, such as the Convention on the Rights of the Child, into domestic law. It also offers a comparative analysis with practices in other countries, shedding light on unique approaches to balancing parental accountability and child welfare. This study underscores the importance of a comprehensive legal framework to ensure stability, emotional support, and non-discrimination, creating a nurturing environment where children can thrive.